2016
DOI: 10.3748/wjg.v22.i2.874
|View full text |Cite
|
Sign up to set email alerts
|

Hepatocyte transplantation program: Lessons learned and future strategies

Abstract: This review aims to share the lessons we learned over time during the setting of the hepatocyte transplantation (HT) program at the Hepatic Cell Therapy Unit at Hospital La Fe in Valencia. New sources of liver tissue for hepatocyte isolation have been explored. The hepatocyte isolation and cryopreservation procedures have been optimized and quality criteria for assessment of functionality of hepatocyte preparations and suitability for HT have been established. The results indicate that: (1) Only highly viable … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
45
0
2

Year Published

2016
2016
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(47 citation statements)
references
References 67 publications
0
45
0
2
Order By: Relevance
“…Current research has shown success in hepatocyte transplantation using neonatal hepatocytes to assist cellular proliferation of injured livers. [31][32][33] A neonatal liver has the full contingent of pluripotent cells necessary to repopulate an ECM with parenchymal hepatocytes and non-parenchymal cells including sinusoidal endothelial cells, stellate cells and biliary epithelial cells. This method may have a distinct advantage over similar methods using pluripotent stem cells 34 as the neonatal liver cells have already traversed to the hepatic lineage and should be primed for cell-tomatrix communication to enhance proliferation, localization, and functionality.…”
Section: Discussionmentioning
confidence: 99%
“…Current research has shown success in hepatocyte transplantation using neonatal hepatocytes to assist cellular proliferation of injured livers. [31][32][33] A neonatal liver has the full contingent of pluripotent cells necessary to repopulate an ECM with parenchymal hepatocytes and non-parenchymal cells including sinusoidal endothelial cells, stellate cells and biliary epithelial cells. This method may have a distinct advantage over similar methods using pluripotent stem cells 34 as the neonatal liver cells have already traversed to the hepatic lineage and should be primed for cell-tomatrix communication to enhance proliferation, localization, and functionality.…”
Section: Discussionmentioning
confidence: 99%
“…Cryopreserved cells or tissues possess some advantages for basic research and current and future clinical applications. With the constant availability of cryopreserved cells and tissues, extensive quality testing can be performed to determine the suitability of the cells or tissue for transplantation without the need to obtain fresh samples 7 . The successful cryopreservation of cells and tissues has been gradually increasing in recent years with the use of CPAs and temperature control equipment (Table 1).…”
Section: Introductionmentioning
confidence: 99%
“…Hepatocytes are not easily cultured in vitro and are susceptible to freeze‐thaw damage . The most important restriction to their use, however, is the difficulty that isolation of a sufficient quantity of metabolically active, high quality cells presents . Not only is there a universal shortage of donor livers on which cell harvests may be performed, but the fact that hepatocytes are typically harvested from livers not suitable for transplantation makes quantity and quality of cells obtained highly variable .…”
Section: Use Of Primary Hepatocytes Versus Stem Cellsmentioning
confidence: 99%